Personal utility in genomic testing: is there such a thing? - Bunnik, M. (Journal of medical ethics, 2015)
In ethical and regulatory discussions on new applications of genomic testing technologies, the notion of ‘personal utility’ has been mentioned repeatedly. It has been used to justify direct access to commercially offered genomic testing or feedback of individual research results to research or biobank participants. Sometimes research participants or consumers claim a right to genomic information with an appeal to personal utility. As of yet, no systematic account of the umbrella notion of personal utility has been given. This paper offers a definition of personal utility that places it in the middle of the spectrum between clinical utility and personal perceptions of utility, and that acknowledges its normative charge. The paper discusses two perspectives on personal utility, the healthcare perspective and the consumer perspective, and argues that these are too narrow and too wide, respectively. Instead, it proposes a normative definition of personal utility that postulates information and potential use as necessary conditions of utility. This definition entails that perceived utility does not equal personal utility, and that expert judgment may be necessary to help determine whether a genomic test can have personal utility for someone. Two examples of genomic tests are presented to illustrate the discrepancies between perceived utility and our proposed definition of personal utility. The paper concludes that while there is room for the notion of personal utility in the ethical evaluation and regulation of genomic tests, the justificatory role of personal utility is not unlimited. For in the absence of clinical validity and reasonable potential use of information, there is no personal utility.